MARITAL DISHARMONY IN JACKIE COLLINS’ NOVEL HOLLYWOOD WIVES - Nuri Buwono; Andang Suhendi; Zulfan Sahri (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2017)
Abstract The study is centered on marital disharmony reflected from the protagonist, Elaine Conti, in running her family life. Marital disharmony can occur if the spouses do not spend sufficient time together or if they do not have common interests. Elaine Conti is married to a famous actor of Hollywood, Ross Conti, but their marriage is not running smoothly as Elaine cannot put herself in a proper place of a good wife. The analysis shows that any relationship is hard and any relationship can lead to a range of arguments and difficulties. However when it comes to marriage all of these difficulties are exacerbated, which is a shame because the steaks are also exacerbated. A break up means potentially losing home, meaning legal and financial difficulties and it may mean putting the rest of the family and particularly any children through a lot of difficulties. This is seen that Elaine, the protagonist, cannot play her role as a good wife in the family caused by her extravagant lifestyle, committing adultery and insatiable passion.  The method used here is Descriptive Qualitative proposed by Koul (1990) and the results show that her attitudes in running a marriage life have caused a marital disharmony, in line with the main theory referred to as the base of the study proposed by Hendrix stating that extravagance, adultery and insatiable passions are the main causing factors to marital disharmony. Keywords: disharmony, marriage, extravagance, adultery, passion